Existência de atratores globais para problemas parabólicos envolvendo o Laplaciano e o p-Laplaciano - Débora Aparecida Francisco Albanez (2010)
In this work we show the existence of global attractors for one-dimensional parabolic problems involving Laplacian operator and p-Laplacian operator, with p >2